2020 8th International Conference on Cyber and IT Service Management (CITSM) 2020
DOI: 10.1109/citsm50537.2020.9268843
|View full text |Cite
|
Sign up to set email alerts
|

Effect Digital Learning on Student Motivation during Covid-19

Abstract: This study aims to measure the level of student motivation in using digital learning during Covid-19. In conducting this research, the structural equation modeling method is used by using the Partial Least Square (PLS) theory, the software used is SmartPLS 2.0. with the number of responding 190 students. From the proposed hypothesis, there is a significant value, namely digital learning has a positive impact on student learning motivation. The novelty of this study explores the impact of digital learning on st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
13

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 18 publications
0
21
0
13
Order By: Relevance
“…Beberapa kajian lepas telah dijalankan bagi melihat motivasi pelajar sepanjang pembelajaran dalam talian semasa pandemik Covid-19 (Abdul Aziz & Aida, 2020;Ida et al, 2020). Selaras dengan teori kepentingan motivasi, motivasi pelajar IPT didapati sangat penting dalam memastikan mereka bersedia mengikuti pembelajaran secara dalam talian.…”
Section: Motivasiunclassified
See 3 more Smart Citations
“…Beberapa kajian lepas telah dijalankan bagi melihat motivasi pelajar sepanjang pembelajaran dalam talian semasa pandemik Covid-19 (Abdul Aziz & Aida, 2020;Ida et al, 2020). Selaras dengan teori kepentingan motivasi, motivasi pelajar IPT didapati sangat penting dalam memastikan mereka bersedia mengikuti pembelajaran secara dalam talian.…”
Section: Motivasiunclassified
“…Selain itu, kajian lepas juga menunjukkan terdapat hubungan yang signifikan antara kesediaan pelajar dengan motivasi pelajar terhadap pembelajaran secara dalam talian (Abdul Aziz & Aida, 2020). Pembelajaran secara dalam talian yang menggunakan teknologi digital juga dilihat memberi kesan yang positif terhadap motivasi pelajar sepanjang pandemik (Ida Faridah et al, 2020). Hal ini disebabkan pelajar lebih bermotivasi semasa belajar sambil mengaplikasikan pembelajaran menggunakan teknologi digital.…”
Section: Motivasiunclassified
See 2 more Smart Citations
“…16, Issue 2 (Aug) 2021 learning by relying on teaching materials as students can study anytime and anywhere, both online and offline (Buabeng-Andoh, 2018). Most of the studies done by researchers all over the world proved that there is a significant positive value of digital learning on students' motivation to learn (Faridah et al, 2020). However, after more than a year of utilizing ODL, some researchers showed that students perceived online education to be less satisfying than on-campus education and rated their interests as declining.…”
Section: Students' Motivationmentioning
confidence: 99%